-8(y+4)=10y+4

Apply the distributive property.

-8y-8⋅4=10y+4

Multiply -8 by 4.

-8y-32=10y+4

-8y-32=10y+4

Subtract 10y from both sides of the equation.

-8y-32-10y=4

Subtract 10y from -8y.

-18y-32=4

-18y-32=4

Add 32 to both sides of the equation.

-18y=4+32

Add 4 and 32.

-18y=36

-18y=36

Divide each term in -18y=36 by -18.

-18y-18=36-18

Cancel the common factor of -18.

Cancel the common factor.

-18y-18=36-18

Divide y by 1.

y=36-18

y=36-18

Divide 36 by -18.

y=-2

y=-2

Solve for y -8(y+4)=10y+4